UPAYA MENINGKATKAN HASIL BELAJAR IPS MELALUI MEDIA GAMBAR PADA SISWA KELAS II MIN MELIKAN GUNUNGKIDUL (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2016)
This study aims to increase interest in social studies. By using images media, students in class of 2 MIN Melikan Gunung be pleased to learn IPS and IPS easy to understand the concept, so that social studies is no longer a subject that feels spacious and tough, but being a pleasant subjects. This research was conducted in MIN Melikan, Gunung Kidul, Total students is nine, comprising four boys and five female students. This research is a classroom action research (PTK), with three cycles, each cycle consisting of four phases: planning, action, observation and reflection. Data collected through observation, tests, interviews, and documentation. Analysis of the data used is data reduction, data presentation and conclusion. The results of the analysis of the action pre-cycle, the first cycle, second cycle and third cycle, suggesting that the social studies learning by using media images are varied, such as document family form of ID card, driver's license, KK and pictures of family photos, family tree, actually may increase interest in learning IPS, this can be proved by the progress of learning interest pre-cycle excellent 3 excellent 2 students, the first cycle of either 4 excellent 3 students, the second cycle of either 2 excellent 5 students, the third cycle of either 1 splendidly 6 students, the average yield tests pre-cycle, the end of the test the first cycle, second cycle and third cycle is always increasing. Results of preliminary tests first cycle of pre-cycle average 5.33 average test results the end of the first cycle of 7.11, the average yield of the end of the second cycle test 8.00 and the average yield of the end of the third cycle test 9.22. Social studies lesson in class of II MIN Melikan, Gunung Kidul, which was supposed to be broad and boring lessons interesting and fun student.